Impact Force Evaluation of the Derailment Containment Wall for High-Speed Train through a Collision Simulation - Hyun-Ung Bae; Kyung-Min Yun; Jiho Moon; Nam-Hyoung Lim (Advances in Civil Engineering)
Fatal train accidents usually involve derailments or collisions. These derailment/collision accidents are infrequent. However, the damage due to derailment can be catastrophic. Derailment containment walls are usually used in Korea to minimize such damages. However, the impact forces that are needed to design the derailment containment walls were not well defined, and only limited studies were conducted for the behavior of the derailment containment walls. In this study, the focus was made on the impact force analysis of the containment wall through a series of 3D collision simulation after train derailment. Finite element modeling was conducted to analyze the dynamic behavior of the derailed train that collides with a structure such as containment wall using the LS-DYNA analysis software application. The FE models of car bodies, bogie frames, and wheel sets were created such that full conformity was achieved between their numerical models and actual vehicles with respect to the masses and principal mass moments of inertia. In addition, various installation situations of the containment wall were considered for the collision simulation. Finally, the economical alternative method to reduce the impact force was proposed.